Christianity and sexuality in the early modern world - Wiesner, Merry E., 1952- author.
1 online resource.
Keywords: "Christianity and Sexuality in the Early Modern World surveys the ways in which people from the time of Luther and Columbus to that of Thomas Jefferson used Christian ideas and institutions to regulate and shape sexual norms and conduct, and examines the impact of their efforts"--